Influence of the Different Carbon and Nitrogen Sources on the Production of Biodiesel by Oleaginous Fungi Aspergillus terreus, Aspergillus fumigatus (Baghdad Science Journal, 2021)
In the present study, the growth and total lipid contents of two oleaginous fungal isolates Aspergillus terreus, Aspergillus fumigatus were compared in different nitrogen and organic carbon sources.  Artificially the fungi were cultured on media consisting of various mono- or di- or polysaccharides and  peptone or yeast extract as elementary sources for carbon and nitrogen, respectively. Media containing sucrose /yeast extract or glucose/ yeast extract were the most effective for lipid production from fungal, during  two weeks  incubation period, the highest biomass of dry weight was (19.6 , 18.8) g / L , (25.8 , 30.5) g /L  and  lipid yield (1, 0.97 )g/L, (0.65, 0.65) g/ L for two isolates Aspergillus terreus and Aspergillus fumigatus  respectively then followed maltose/ yeast extract then  starch / yeast extract .Analysis of fatty acid produced by two fungal isolates  using Gas Chromatography  showed the existence of a wide range of fatty acids, these fatty acids were together saturated and unsaturated. The results revealed that the unevenness in the fatty acids composition mainly depends on the type of carbon and nitrogen sources. The existence of saturated and mono saturated fatty acids in A.fumigatus, A. terreus prove that they are  good candidate for biodiesel production.The analysis of fatty acid from the fungal growth showed the existence of a wide range of fatty acids   Palmitic ,Oleic acids , stearic acid and linoleic acid     together saturated and unsaturated. The results revealed that the unevenness in the fatty acid composition mainly depends on the type  of carbon  and nitrogen sources. The presence of saturated and mono saturated fatty acid in  A.fumigatus , A. terreus prove that it is a good candidate for biodiesel production.